2017
DOI: 10.1002/lio2.80
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent respiratory papillomatosis (RRP)–time for a reckoning?

Abstract: ObjectivesRecurrent respiratory papillomatosis (RRP) is a rare disease, but one with severe morbidity and occasional mortality. The aetiological agent is human papillomavirus (HPV), and HPV types 6 and 11 account for over 90% of all cases. In the active phase of the disease, patients require multiple hospital admissions for surgical removal or ablation of these benign tumors, which are likely to obstruct the airways if left unchecked. Long‐term sequelae include scarring of the vocal cords, change in voice timb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 21 publications
1
24
0
1
Order By: Relevance
“…Some surgeons have conducted such interventions under a research protocol and have published their observations. Several showed a serologic response [36,37] to the vaccine and an increase in the time between surgeries [5,6,38,39]. Hermann et al [7] and Milner et al [8]found no such difference.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Some surgeons have conducted such interventions under a research protocol and have published their observations. Several showed a serologic response [36,37] to the vaccine and an increase in the time between surgeries [5,6,38,39]. Hermann et al [7] and Milner et al [8]found no such difference.…”
Section: Plos Onementioning
confidence: 99%
“…Several years have passed since the study was executed and the preliminary results were communicated via poster and oral presentation. Since then there has been interest in the feasibility of using the quadrivalent HPV (qHPV) vaccine as a treatment modality for RRP [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Patient subgroups not relevant to our study were excluded from the study population before statistical analysis along with patients with any malignant disease or pre-malignant laryngeal lesions (n=3) [13]. In the meta-analysis, we further excluded seven patients with less than 24 months of follow-up after vaccination (four patients from Hočevar-Boltežar et al [28] and three patients from Goon et al [31])…”
Section: Data Items and Collection Processmentioning
confidence: 99%
“…Only a few original studies addressing the therapeutic use of the HPV vaccine as treatment for RRP have been published [13,16,[25][26][27][28][29][30][31][32] along with a small number of case reports [33][34][35][36][37][38][39]. The reported outcomes vary, and a proposed large-scale multicenter study has not yet been undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…Известно, что в определенных клеточных системах гены ВПЧ, кодирующие структурные белки вириона L1 и L2, способны осуществлять не только синтез соответствующих белков, но и формирование так называемых вирусоподобных частиц (VLP-viruslikeparticles). Эти частицы, не содержащие в своем составе ДНК вируса, обладают очень выраженной иммуногенной активностью [48].…”
unclassified